Towards a theoretical foundation for a multidisciplinary economics - Piet Keizer (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
This article analyses the primary motives that set people in motion, namely the economic, the social and the psychic motive. By integrating the three basic analyses, we formulate an integrated paradigm and analysis that can flinction as a theoretical basis for a multidisciplinary economics. Orthodox economics analyses the force that results from the confrontation between humans and their natural environment. In such a situation humans are driven to maximise the utilities they derive from consuming scarce goods. Orthodox sociology analyses the force that results from the confrontation between (different groups of) humans. In such a situation humans are driven to maximise the status they derive from their position in the social structure, under the constraint of the norms that are set by the prevailing culture. Orthodox psychology analyses the force that results from the confrontation between the 'I' of a person and his 'self. We distinguish between an actual and a true self The 'I' is a rational decision making centre that is assumed to minimise the difference between the actual self and the true self, thereby maximising the respect of the true self for the actual self (self-respect). The drive to maximize self-respect is contrianed by the limited power of the will. This article integrates the three orthodox approaches into one analytical process on the micro level and one on the macro level. Individuals operate in a cultural context, which is determined on the macro level, but have some discretionary room to take their own decisions.
Keywords: 330; Economic; Scarcity; Social; Status; Psychic; Self-Respect; Rational; Will- Power; Multi-Disciplinary Economics; Isolated Abstraction